Performance and Emission of Single Cylinder Four-Stroke Diesel Engine Using Waste Animal Fat (International Journal of Innovative Research in Engineering & Management, 2023)
Synthesis of biodiesel from waste animal  fat was the first step in this research. Biodiesel was made  using a traditional chemical process called  transesterification. In transesterification process pure fat  was reacted with methanol in presence of KOH as catalyst.  For every 100 ml of pure liquid fat 1 gram of KOH with  20ml of methanol was used for reaction at around 60oc  temperature. Following the production of biodiesel, blends  of biodiesel and neat diesel in various mixing ratios, such  as AFME5 (95 % D+5 % BD), AFME10 (90 % D+10 %  BD), and AFME20 (80 % D+20 % BD) were prepared for  carrying out the performance and emission tests on four stroke single-cylinder diesel engine. The primary physico chemical properties such as Calorific value, density,  kinematic viscosity and CFPP of fat-based biodiesel and  its blends were determined prior to testing. All of the  properties measured were found to be in agreement with  ASTM requirements.
Keywords: Biodiesel; Neat diesel; Transesterification; AFME; Engine tests; Performance parameters; Emissions; CFPP